2015
DOI: 10.1007/s11694-015-9279-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grinding methods for flour characterisation of Pusa 1121 basmati rice brokens

Abstract: This study attempted to evaluate dry, semi dry and wet grinding methods on flour characteristics of Pusa 1121 basmati rice brokens. The flour obtained through grinding methods was characterized based on for physicochemical, morphological, pasting, flow properties, X-ray diffraction and Fourier transform infrared (FTIR) spectroscopy. Mean particle size of dry ground rice flour was higher in comparison to other grinding methods adopted. Amylose content (%) of flour analysed for different method dry, semi dry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Studies have shown that the particle size of flour could affect the flour properties and bread quality. Singh and Prasad 27 reported that small flour particles would produce a dough with low ductility and fluidity. And Cappelli et al 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the particle size of flour could affect the flour properties and bread quality. Singh and Prasad 27 reported that small flour particles would produce a dough with low ductility and fluidity. And Cappelli et al 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that the particle size of flour could influence the flour's properties. Smaller flour particles (<75 μm) resulted in poor extensibility and flowability of dough, while larger particles (>200 μm) were difficult to hydrate and gelatinize, which all affected the formation of gluten network structure (Singh & Prasad, 2016; Qin et al ., 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to head or secondgrade head rice, the broken rice pieces make up 20-30% of milled rice and are sold at a very low price ( Raina et al 2005). This underutilized by-product of the rice milling industry can be used to improve financial outcomes and find new uses for rice-broken kernels ( Singh and Prasad 2015). Important ingredients like starch and oil in broken rice has a protein content of 8-10%.…”
Section: Introductionmentioning
confidence: 99%